1995
DOI: 10.1002/ijc.2910620319
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamic acid: A natural product with potential use in cancer intervention

Abstract: Cinnamic acid, a naturally occurring aromatic fatty acid of low toxicity, has a long history of human exposure. We now show that cinnamic acid induces cytostasis and a reversal of malignant properties of human tumor cells in vitro. The concentration causing a 50% reduction of cell proliferation (IC50) ranged from 1 to 4.5 mM in glioblastoma, melanoma, prostate and lung carcinoma cells. Using melanoma cells as a model, we found that cinnamic acid induces cell differentiation as evidenced by morphological change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
110
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(120 citation statements)
references
References 18 publications
1
110
0
9
Order By: Relevance
“…[42,43] In contrast, cinnamic acid has been shown to down-regulate expression of cell proliferation and anti-apoptotic gene products, although the affects of both high and low concentrations were not examined. [100,101] The redox environment affects cellular signal transduction, DNA and RNA synthesis, protein synthesis, enzyme activation, regulation of the cell cycle, ligand binding, DNA binding and nuclear translocation, and therefore ultimately cell proliferation/ death. [102,103] Transcription factors are active in their reduced form and their translocation to the nucleus is also redox dependent.…”
Section: Antiseptic Activitymentioning
confidence: 99%
“…[42,43] In contrast, cinnamic acid has been shown to down-regulate expression of cell proliferation and anti-apoptotic gene products, although the affects of both high and low concentrations were not examined. [100,101] The redox environment affects cellular signal transduction, DNA and RNA synthesis, protein synthesis, enzyme activation, regulation of the cell cycle, ligand binding, DNA binding and nuclear translocation, and therefore ultimately cell proliferation/ death. [102,103] Transcription factors are active in their reduced form and their translocation to the nucleus is also redox dependent.…”
Section: Antiseptic Activitymentioning
confidence: 99%
“…Cinnamic acid was also pointed out as possessing antitumor activity against human malignant tumors, including melanoma, glioblastoma, adenocarcinoma of the prostate and lung (Liu, Hudgins, Shack, Yin, & Samid, 1995) and colon adenocarcinoma (Ekmekcioglu et al, 1998). Drupanin and baccharin, two cinnamic acid derivatives, were reported as inhibitors of the growth of HeLa-60 cell lines by inducing apoptosis (Akao et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…cinnamic acids, which are found in different natural resources and widely used for diverse medicinal purposes, 3,4 have demonstrated to constitute scaffolds of great interest for the development of new antitumor agents. 5,6 In one hand, quinoline synthetic versatility promotes the development of large diversity of quinoline analogues.…”
mentioning
confidence: 99%
“…2,8 In the case of cinnamic acid, it has been reported that one of its modes of action seems to be inhibition of protein isoprenylation, which blocks mitogenic signal transduction. 4 Still, cinnamic acid analogues have also shown to be antiangiogenic, antileukemic as well as inhibitors of transglutaminase, aminopeptidase N, DNA synthesis, and of a specific tyrosine kinase. 5,9 The introduction of a cinnamic acid moiety has also demonstrated to boost the antitumor activity of parent antitumor compounds; for instance, distamycin A, 2 in Figure 1, (IC 50 = 7.2 ng/mL) which includes a cinnamoyl functionality, showed antileukemic activity superior to that presented by tallimustine, 3 in Figure 1 (IC 50 = 50.3 ng/mL).…”
mentioning
confidence: 99%